Molecular characterization of rectal isolates of carbapenemase-negative carbapenem-resistant enterobacterales obtained from ICU patients in Kuwait by whole-genome sequencing. Issue 9 (3rd September 2021) - Al Fadhli, Amani; Jamal, Wafaa; Rotimi, Vincent O.
Abstract : Introduction. Carbapenem-resistant enterobacterales (CRE) are listed among the most urgent antibiotic resistance threats. Hypothesis. Previous studies on the mechanisms of CRE in Kuwait have focused on carbapenemases. There have been no studies on non-carbapenemase-producing CRE in Kuwait. Aim/Gap Statement. The aim of this study was to investigate the genetic characteristics of non-carbapenemase-producing carbapenem-resistant enterobacterales (NCPE) isolates using whole-genome sequencing (WGS). Methodology. Fourteen confirmed NCPE isolates that were negative for genes encoding carbapenemase production by polymerase chain reaction (PCR) assays using rectal swabs from intensive care unit patients were characterized using phenotypic, PCR and WGS methods. Susceptibility testing was performed via Etest and clonality via multi-locus sequence typing (MLST). Results. All of the isolates were resistant to ertapenem; 78.6 % were resistant to imipenem, meropenem and trimethoprim–sulfamethoxazole. Resistance to the other antibiotics was variable, ranging from 28.5 (colistin) through 50 (tigecycline) and 64.3 (amikacin) up to 85.7 % against both amoxicillin–clavulanic acid and ciprofloxacin. WGS detected several resistance genes mediating the production of β-lactamases, genes encoding an outer-membrane porin permeability mutation resulting in reduced susceptibility to β-lactams, including carbapenems, and genes for multidrug-resistant (MDR) efflux pumps. The isolates also possessed global activator protein MarA, which mediated reduced permeability to β-lactams. The existence of β-lactamase genes, overexpression of MDR efflux pumps and reduced permeability mediated by the porin genes were responsible for carbapenem resistance. Conclusions. This finding reflects the superior detection capabilities offered by WGS analysis, which can be used to complement traditional methods and overcome their limited resolution in clinical settings.